The Effect of Covid-19 Vaccine Service Quality on Community Satisfaction at the Hauranggung Health Center, Garut Regency - Ikeu Kania (Budapest International Research and Critics University, 2022)
The Covid-19 pandemic has compelled public service institutions, notably Puskesmas, to provide Covid-19 immunization services to the public. The study's goal was to investigate the impact of service quality on community satisfaction in the Covid-19 vaccine service at the Hauranggung Health Center in Garut Regency. By employing a quantitative methodology, conducting research via a survey, and distributing questionnaires to 100 respondents via a purposive sampling method. Using the SPSS 25 analysis tool, the data was then analyzed using multiple regression. The findings revealed that four of the five service quality criteria, namely responsiveness, dependability, integrity, and fairness, had an impact on the satisfaction of people who got immunization services at the Hauranggung Garut Health Center. The reliability variable has no effect on community satisfaction. The responsiveness variable has the most impact on community satisfaction in the Covid-19 immunization service at the Hauranggung Health Center in Garut Regency, while reliability has the least effect.